Anesthetic Management of a Patient With an Incidental Vallecular Cyst: A Case Report - Jibran Ikram; Aariya Srinivasan; Ayesha Zahid; Sabry Ayad (Clinical Case Reports)
ABSTRACT Vallecular cysts are rare, benign lesions of the epiglottis and adjacent structures, often asymptomatic but with the potential to cause airway obstruction during anesthesia. We report the case of a 50‐year‐old female undergoing elective laparoscopic hysterectomy, during which an incidental vallecular cyst was identified during intubation. This case highlights the challenges in airway management and the need for meticulous planning to ensure patient safety. Early diagnosis and multidisciplinary management were essential for favorable outcomes.